Blake Set to Music - Fitch, Donald (Berkeley, CA : University of California Press, 2020)
This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1990.
Frontmatter -- Contents -- List of Sources -- List of Abbreviations -- Introduction -- Alphabetical list of Entries by Composer -- Index of Blake Titles -- Index of Performing Combinations -- Index of Translated Texts -- Index of Names
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 23. Apr 2021).
JSTOR
Keywords: Blake, William, -- 1757-1827 -- Musical settings -- Bibliography; Blake, William, -- 1757-1827; NON-CLASSIFIABLE.; Musical settings; Bibliographies